A Study on Challenges and Prospects of Women Entrepreneurs in India - Naila Pereira; Poonam J. Sadekar; Vaishnavi Ramanujam (Recent Advances in Commerce, Management, and Tourism, 2023)
Women entrepreneurs play a remarkable role within the global business environment contributing to continuous economic development and social advancement. Women entrepreneurs are the doubtless promising human resource within the 21st Century. Women stand tall to attain equal rights and positions within the society by venturing into innovative and lucrative entrepreneurial opportunities although are faced with multi-dimensional hurdles. In view of the above this paper aims to review literature studies on women entrepreneurs in India and investigates the prospects, challenges and problems faced by them. The findings of this study reveal enhanced educational opportunities, gender equality, shifting attitude of the society, spouse/family support, holistic development, and government initiatives as the reasons for women empowerment. This successively has reinforced the status of women by creating a desire for being self-reliant which has triggered and accelerated the process of women entrepreneurship.